2015
DOI: 10.1159/000381431
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Basis for Developing Diverticular Disease, Diverticulitis, and Diverticular Bleeding

Abstract: Diverticula of the colon are pseudodiverticula defined by multiple outpouchings of the mucosal and submucosal layers penetrating through weak spots of the muscle coat along intramural blood vessels. A complete prolapse consists of a diverticular opening, a narrowed neck, and a thinned diverticular dome underneath the serosal covering. The susceptibility of diverticula to inflammation is explained by local ischemia, translocation of pathogens due to retained stool, stercoral trauma by fecaliths, and microperfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 58 publications
1
51
0
3
Order By: Relevance
“…[102][103][104] Alterations in collagen composition and content as well as connective tissue metabolism have been identified in colons of patients with diverticulosis. 105 Reduced numbers of ganglionic and neuronal cells, 106 as well as imbalances in neurotrophic factors and neuropeptides such as serotonin and acetyl choline, are also found in patients with diverticular disease. [107][108][109] These alternations might cause symptoms in patients with diverticulosis.…”
Section: Alterations In Colonic Neuromusculaturementioning
confidence: 99%
“…[102][103][104] Alterations in collagen composition and content as well as connective tissue metabolism have been identified in colons of patients with diverticulosis. 105 Reduced numbers of ganglionic and neuronal cells, 106 as well as imbalances in neurotrophic factors and neuropeptides such as serotonin and acetyl choline, are also found in patients with diverticular disease. [107][108][109] These alternations might cause symptoms in patients with diverticulosis.…”
Section: Alterations In Colonic Neuromusculaturementioning
confidence: 99%
“…More recently, evidence rises for an enteric neuropathy in DD, characterized by reduced nerve cells (oligo-neuronal hypoganglionosis), decreased intramuscular nerve fibers and altered neurochemical coding [ 6 8 ]. Since DD is associated with abnormal intestinal motility patterns [ 9 , 10 ] it is suggested that the disease could be associated with and possibly triggered by an underlying enteric neuropathy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since nAchRs are critical for gastrointestinal motility (Galligan and North, 2004) and DD is characterized by disturbed intestinal motility (Parks and Connell, 1969;Wedel et al, 2015), we investigated the mRNA expression of those nAchR subunits known to be present in the ENS: the ligand binding nAchR subunits α3, α5, α7 and the structural nAchR subunits β2, β4. While the structural nAchR subunit β4 was down-regulated both at gene and protein level in patients with DD compared to controls, the other subunits remained unaffected.…”
Section: Enteric Expression and Regulation Of Nachr Subunits In Ddmentioning
confidence: 99%